Safety evaluation of a collapsed turbine wind on the buried pipeline. (December 2017) - Huang, Dong; Zhao, Yu; Chen, Y.L.
Abstract: In order to study the impact of the collapse of a wind turbine on the buried pipeline, three conditions are explored. With the formula of penetrating power, the impact force and impact depth resulted from the wind turbine collapse are estimated for safety evaluation. The evaluation results show that if the impact is only from the wind turbine collapse, the pipeline is not damaged, but it is difficult to ensure the normal operation of the pipeline. If the damage is caused by the wing turbine with blades or only by blades, the downward penetrating force is so large that the pipeline is directly sheared off. Although the probability of wind turbine collapse is low, it is harmful to the pipeline and appropriate protective measures should be adopted. Highlights: With respect to the safety hazard of wind turbine collapse on buried pipelines in the China-Myanmar pipeline project. Variations of stress and strain parameters of the pipeline under impact load have been analyzed. If the impact is from the wind turbine collapse only, the pipeline is not damaged even there is a large change in the ovality of the pipe. If the damage is caused by the wind turbine and blades or by the blades only, the pipeline can be directly sheared off.